Educational inequalities in mental disorders in the Czech Republic: data from CZEch Mental health Study (CZEMS) - Kuklová, Marie; Kagstrom, Anna; Kučera, Matěj; Mladá, Karolína; Winkler, Petr; Cermakova, Pavla (Social psychiatry and psychiatric epidemiology, 2021)
PURPOSE: We aimed to study the association of educational attainment with occurrence of mental disorders in the Czech Republic. METHODS: Data were derived from the CZEch Mental health Study (CZEMS), a cross-sectional study of community-dwelling individuals. Mental disorders were assessed with Mini International Neuropsychiatric Interview (M.I.N.I.), and information on completed education was acquired as a part of a paper and pencil interview. Logistic regression was used to estimate odds ratio (OR) with 95% confidence intervals (CI) for the association of educational attainment with all mental disorders as well as with specific groups (affective, anxiety, alcohol use and substance use disorders), stepwise adjusting for socio-demographic, social and health-related characteristics. RESULTS: We studied 3175 individuals (average age 50 years, range 18-96 years; 54% women). Compared to individuals with higher education, those educated below high school graduation had higher odds of mental disorders (OR 2.07; 95% CI 1.58-1.71), even after adjustment for all covariates (OR 1.64; 95% CI 1.21-2.23). Education showed the strongest association with alcohol use disorders, even when covariates were adjusted for, but was not related to anxiety disorders. The association of education with affective as well as substance use disorders was explained by covariates. CONCLUSIONS: Interventions aimed at reducing the burden of mental disorders should target individuals with low education. Strategies to improve population mental health need to go hand in hand with policies to enhance education as well as reduce alcohol consumption in the Czech Republic.
Keywords: Young Adult; Cross-Sectional Studies; Alcoholism; Male; mladý dospělý; Mental Disorders; Mental disorder; alkoholismus; Adolescent; Česká republika; Inequality; Mental Health; Adult; Aged; dospělí; duševní zdraví; mužské pohlaví; senioři; duševní poruchy; stupeň vzdělání; mladiství; Czech Republic; senioři nad 80 let; lidé; Population; ženské pohlaví; Educational Status; Humans; průřezové studie; Aged, 80 and over; Education; Female; lidé středního věku; Middle Aged